Effects of metalworking fluid exposure on respiratory and skin health and an awareness program to protect workers in a metal machining factory - Jabbar, Mohammed Abdulrazzaq (2018)
Introduction: Metalworking fluid (MWF) was used during machining processes such as cutting, turning, and grinding of metals and it works to provide lubrication and cooling effects to the machines and products. The workers in the production section were exposed to the fluid through variant routes as inhalation and direct skin contacts. The exposure could have lead to respiratory and skin health complaints. Objectives: Phase I of the study aimed to determine the exposed workers’ respiratory and skin health status as compared to unexposed and associate that with the level of exposure. Phase II aimed to evaluate the effectiveness of the individual awareness program on exposed workers by enhancing their compliances towards using the protective methods regularly and properly. Methodology: Phase I, 298 exposed with 97 unexposed workers were involved in a comparative cross-sectional study. Measurements of individual respiratory exposure to MWF and Heavy metals (Cr and Ni) were carried out using NIOSH 5524 and NIOSH 7300 methods respectively. Assessment of individual skin exposure was carried out suing dermal exposure assessment method (DREAM). Respiratory and skin health were assessed using standardized questionnaires. Phase II, 240 of exposed workers, involved in phase I, were selected and allocated randomly for experimental and control groups in a randomized controlled trial. Assessment of workers’ compliances to use the preventive measures on pre and post-intervention levels were carried out in addition to respiratory and skin health assessment. Results: Phase I showed the prevalence of respiratory symptoms among exposed workers were significantly higher nasal complaint (p<0.001) cough (p<0.001) cough with phlegm (p=0.001) as compared to unexposed workers. In the same time, the exposed workers had significantly higher reporting rate of skin symptoms on hand (p<0.001) forearm (p<0.001) and front torso (p=0.001) as compared to the unexposed group. Phase II of the study revealed that the intervention group on posttest had significantly higher likelihood towards using face mask (OR 1.75 CI 1.01-3.00), cleaning working area (OR 1.81 CI 1.01-3.04), changing working uniform (2.01 CI 1.37-3.61), and wearing gloves (OR 1.61 CI 1.03-2.90) as compared to the control group. On the other hand, on posttest level, the intervention group showed lower prevalence of respiratory symptoms nasal complaints (p=0.042), cough (p=0.014), and cough with phlegm (p=0.026) as compared to the control group. The intervention group similarly showed significantly lower skin complaints on hands (p=0.039), forearms (p=0.001), and front torso (p=0.008) as compared to control group. Conclusion: respiratory and skin exposure to MWF leads to several respiratory and skin health complaints among workers in this metal machining factory and individual awareness program was effective method to improve the workers’ compliances toward using preventive methods.